Identification of Klebsiella species by Polymerase Chain Reaction and Restriction Fragment Length Polymorphism along with Their Antibiotic Resistance Pattern (IAHS Medical Journal, 2026)
Background: Klebsiella species are closely related bacteria that can cause various multidrug resistant health care infections. The aim of the study was to detect different Klebsiella species by Polymerase Chain Reaction (PCR) and Restriction Fragment Length Polymorphism (RFLP) along with their antibiotic resistance pattern.Materials and methods: This cross-sectional study was carried out in the Department of Microbiology of Dhaka Medical College, Dhaka, Bangladesh from January 2021 to December 2021.Total 340 different clinical samples were collected. Organisms were isolated and identified by culture, Gram staining and biochemical tests. PCR and RFLP were done to differentiate Klebsiella species. Antibiotic susceptibility pattern was determined by disc-diffusion method.Results: Fifty-seven Klebsiella spp. were isolated and among them 56 (98.25%) were identified as K. pneumoniae and one (1.75%) as K. oxytoca by biochemical tests whereas PCR revealed that 55 (96.49%) were K. pneumoniae, one (1.75%) was K. ozaenae and one (1.75%) was K. oxytoca. Following HaeIII and taqI digestion, all the K. pneumoniae and K. ozaenae demonstrated a single RFLP pattern whereas K.oxytoca demonstrated different pattern. Regarding antimicrobial resistance pattern, Klebsiella spp. showed higher resistance to ceftazidime and ceftriaxone (91.23%), cefepime (87.72%), aztreonam (68.42%), amikacin (63.16%) followed by imipenem (36.84%) and tigecycline (21.05%).Conclusion: This study portrayed the antibiotic resistance pattern of Klebsiella species demanding the monitoring of strict antibiotic policy. PCR and RFLP may be suitable method to identify Klebsiella species.IAHS Medical Journal Vol 8(1), June 2025; 26-31